How the International Organizations have Influenced the Era of Globalization - Muskaj, Blerina (Acta Universitatis Danubius. Relationes Internationales, 2024)
Finally, the role and mission of the UN in the new world order in the above formation is not conditioned by the capacity, professionalism of the United Nations, but by the philosophy of international relations applied by great powers, as well as by the imposition of a necessity of the international geopolitical environment. The flow of events still shows that major powers continue to consider an Organization II as a forum for exchanging opinions and ideas for international diplomats as a place of technical procedures or limited contributions to humanitarian issues. Regroups, military-strategic alliances, such NATOs are endowed with the entire premise and chances of playing a primary role in the new, progressively developing and formed land order. In this presentation, it is presented the new world order in the era of globalization by analysing the international organizations such as NATO and FMN, UN. OKB on the world order is seen as an organization that follows the Great Powers Applied International Rules.